Copper-based electrocatalyst and preparation method and application thereof
By growing copper-based micron wires in situ on a copper support, a copper-based electrocatalyst with high activity and stability was prepared, which solved the problems of catalyst stability and HMF instability in the prior art, and achieved efficient HMF oxidation and FDCA production.
Patent Information
- Application Number
- CN202411534709.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-11
AI Technical Summary
The existing electrocatalytic oxidation of 5-hydroxymethylfurfural (HMF) to produce 2,5-furandicarboxylic acid (FDCA) has high cost, mainly limiting the price, activity and stability of the catalyst and the Faraday efficiency of the reaction. Copper (Cu) has stability problems as a potential catalyst, and HMF is unstable, making it easy to spontaneously decompose and polymerize in a liquid phase environment.
A copper-based electrocatalyst is used, consisting of copper-based microwires grown in situ on a copper support. The inside of the microwire is elemental copper and the surface is copper oxide nanosheets. The catalyst is prepared by electrochemical method, including electrooxidation, electroreduction and electroactivation steps, and has a large electrochemical active area, strong binding force, strong stability, weak oxygen evolution competition and high energy utilization.
It improves the conductivity and stability of copper-based catalysts, enhances the oxidation capacity of HMF/BHMF, reduces raw material loss and product impurity, and improves the production efficiency and energy utilization of FDCA.
Smart Images

Figure CN119592992A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a copper-based electrocatalyst and a preparation method and application thereof. Background Art
[0002] The electrocatalytic method uses electrical energy as the driving force, avoiding the problems of high temperature and high pressure, external oxygen source, long reaction time and dependence on precious metal catalysts in the traditional thermal catalytic method. In addition, the electrocatalytic method also has the characteristics of controllable cathode and anode reactions, making the electrocatalytic method suitable for a variety of application scenarios, and the products obtained are also widely used. The plastic monomer 2, 5-furandicarboxylic acid (FDCA) can be prepared by electrocatalytic oxidation of 5-hydroxymethylfurfural (HMF), and FDCA is used as a monomer to replace terephthalic acid to produce polyethylene furandicarboxylate (PEF). Compared with terephthalic acid-based plastic polyethylene terephthalate (PET), PEF has better barrier properties and mechanical properties. PEF also has good biodegradability and recyclability, and is more environmentally friendly than PET.
[0003] At present, the process cost of electrocatalytic oxidation of HMF to produce FDCA is still relatively high, and the main limitations are the price, activity and stability of the catalyst and the Faraday efficiency of the reaction. Since nickel (Ni)-based and cobalt (Co)-based catalysts have good activity and stability, the current process of electrocatalytic oxidation of HMF to produce FDCA is still dominated by Ni-based and Co-based catalysts. Since Ni and Co also have good catalytic ability for oxygen evolution reaction, in the high potential / current production process, the competition for oxygen evolution reaction will reduce energy utilization and limit the production efficiency of FDCA. Copper (Cu) is cheap and has excellent conductivity. More importantly, compared with Ni and Co, Cu has low OER activity. In the process of producing FDCA, the competition for oxygen evolution is weak, the energy utilization rate is high, and it can be used for FDCA production at higher potential / current. However, Cu is more prone to loss in alkaline systems than Ni and Co, so how to improve the stability of Cu-based catalysts is an urgent problem to be solved. In addition, HMF is unstable and prone to spontaneous decomposition and polymerization in a liquid environment, resulting in raw material loss and impure products. Compared with HMF, 2, 5-furan dimethanol (BHMF) has stronger stability. Using BHMF as a reaction substrate can reduce raw material loss and improve product purity. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a copper-based electrocatalyst and a preparation method and application thereof. The copper-based electrocatalyst has the advantages of large electrochemical active area, strong binding force, strong stability, strong conductivity, weak oxygen evolution competition and high energy utilization, so that it has good electrocatalytic HMF / BHMF oxidation ability.
[0005] The present invention provides a copper-based electrocatalyst, which consists of a copper carrier and a copper-based microwire in-situ grown on the surface of the copper carrier, wherein the interior of the copper-based microwire is single-element copper, and the surface of the copper-based microwire is copper oxide nanosheet.
[0006] The copper-based electrocatalyst provided by the present invention is in-situ grown on a copper carrier to form micrometer wires composed of internal elemental copper and surface copper oxide nanosheets. The copper-based micrometer wires in-situ generated on the surface are adapted to the lattice of the carrier copper and are more firmly bonded, while also reducing the interface resistance and enhancing the conductivity and stability of the copper-based catalyst. The copper oxide nanosheets in-situ grown on the surface of the micrometer wires can, on the one hand, provide a large electrochemical active area to improve the activity of the copper-based electrocatalyst, and on the other hand, can isolate the direct contact between the internal copper element and the electrocatalytic solution, overcoming the problem of easy loss of copper in alkaline solutions, making the copper-based electrocatalyst more stable. Compared with the copper oxide micrometer wires made by direct calcination, the copper oxide micrometer wires in the copper-based catalyst provided by the present invention have a copper core inside, which has better conductivity and stronger electrocatalytic ability. Compared with the prior art, the copper-based catalyst provided by the present invention has the advantages of high energy utilization, strong binding force, strong stability, large active area and strong conductivity.
[0007] The present invention also provides a method for preparing the copper-based electrocatalyst, comprising the following steps: S1. Electro-oxidation: The copper carrier is immersed in an alkaline solution to perform an electrochemical oxidation reaction, and copper hydroxide microwires are grown in situ on the copper carrier; S2, electro-reduction: the copper hydroxide micro-wires in step S1 are subjected to an electrochemical reduction reaction in the alkaline solution, and the copper hydroxide micro-wires are reduced to form copper micro-wires; S3, electroactivation: the copper microwires in step S2 are subjected to electrochemical oxidation reaction in the alkaline solution, and copper oxide nanosheets are formed on the surface of the copper microwires to obtain copper-based microwires grown in situ on a copper carrier, and a copper-based electrocatalyst is obtained through post-treatment.
[0008] The preparation method of the copper-based electrocatalyst provided by the present invention adopts a pure electrical method, using only alkali as the solute, and fully utilizing the oxidizing property of the alkali through the action of voltage to oxidize the copper element; the method does not require high temperature and high pressure, and can be carried out at room temperature. Compared with other methods for preparing copper and its oxide microwires that require high temperature and high pressure, an external oxygen source, additional metal elements and additives, the method is more environmentally friendly and has lower cost.
[0009] In a possible implementation, the electrical reduction in step S2 adopts a two-step reduction method, the first step of reduction adopts a reduction-oxidation-reduction cyclic voltammetry reduction method, and the second step of reduction adopts a constant potential / constant current reduction method. The reduction-oxidation-reduction cyclic voltammetry reduction method can be used to continuously reconstruct the copper hydroxide microwires during the reduction process, so that the copper-based electrocatalyst has a richer specific surface area; and then the constant potential / constant current reduction method is used to completely convert the copper hydroxide into elemental copper, so that the copper derived from the surface of the carrier is adapted to the carrier copper lattice and the combination is more firm.
[0010] In a possible implementation, the alkali in the alkali solution includes one or both of potassium hydroxide and sodium hydroxide.
[0011] In a possible implementation manner, the concentration of the alkali solution is 0.1-10 M.
[0012] In a possible implementation, the copper carrier includes any one of foam copper, copper tape, copper sheet, copper foil and electrodeposited copper.
[0013] Furthermore, the copper carrier is copper foam, which has good electrical conductivity, high specific surface area and corresponding mass transfer performance. Compared with other copper carriers, copper foam can provide better electrical conductivity and more abundant active sites when used to load electrocatalysts.
[0014] In a possible implementation, the immersion area of the copper carrier in step S1 is 0.5*0.5 to 50*50 cm 2 .
[0015] In a possible implementation manner, the copper carrier in step S1 is first cleaned before being immersed in the alkaline solution, and the cleaning method is to perform ultrasonic cleaning in acetone, ethanol, sulfuric acid, and deionized water in sequence for 10 to 60 minutes.
[0016] In one possible embodiment, the electrochemical oxidation reaction in step S1, the electrochemical reduction reaction in step S2, and the electrochemical oxidation reaction in step S3 are carried out in a three-electrode system or a two-electrode system, wherein the working electrode is a copper support, the counter electrode is a carbon rod or a platinum electrode, and the reference electrode is a Hg / HgO electrode; and the working electrode is a copper support, and the counter electrode is a carbon rod or a platinum electrode in the two-electrode system.
[0017] In a possible implementation manner, the post-treatment in step S3 is drying in an oven at 50-100° C. for 5-20 h.
[0018] Furthermore, when the three-electrode system is used, the electrochemical oxidation reaction in step S1 adopts a constant current / constant potential electrochemical oxidation method, and the current / potential range is 0.01 to 1 A cm -2 / 1~3 V vs. Hg / HgO.
[0019] Furthermore, when the three-electrode system is used, the electrochemical reduction reaction in step S2 is a two-step reaction, the first step is cyclic voltammetry, the potential of the cyclic voltammetry is 0 to -3 V vs. Hg / HgO, and the second step is constant current / constant potential method, the current / potential range is -0.1 to -3 A cm -2 / -1~-5 V vs. Hg / HgO.
[0020] Furthermore, when the three-electrode system is used, the electrochemical oxidation reaction in step S3 is carried out by cyclic voltammetry, and the potential of the cyclic voltammetry is -0.6~1.6 V vs. Hg / HgO.
[0021] Furthermore, when the dual-electrode system is used, the electrochemical oxidation reaction in step S1 adopts a constant current / constant voltage method, and the current / voltage range is 0.01 to 1 A cm -2 / 0.5~2 V.
[0022] Furthermore, when the dual-electrode system is used, the electrochemical reduction reaction in step S2 is carried out by constant current / constant voltage method, and the current / voltage range is -0.1 to -3 A cm -2 / -1~-5 V.
[0023] Furthermore, when the dual-electrode system is used, the electrochemical oxidation reaction in step S3 adopts a constant voltage method with a voltage range of 0.5 to 2 V.
[0024] Furthermore, the reaction time of the electrochemical oxidation reaction in step S1, the electrochemical reduction reaction in step S2 and the electrochemical oxidation reaction in step S3 is 0.1 to 3 h.
[0025] Furthermore, the scanning speed of the cyclic voltammetry is 2 to 200 mV s -1 , the number of scanning circles is 5 to 500.
[0026] The present invention also provides the use of the copper-based electrocatalyst in the electrocatalytic oxidation of HMF / BHMF to produce FDCA and electrolytic hydrogen production.
[0027] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.
[0028] The reagents and raw materials used in the present invention are commercially available.
[0029] The positive and progressive effects of the present invention are: The copper-based electrocatalyst provided by the present invention is a self-supporting monolithic structure, and the copper-based micron wire derived in situ on the copper carrier has a surface layer of copper oxide nanosheets and an inner layer of elemental copper. The elemental copper provides good electrical conductivity, and the micron wire morphology and the nanosheets covered on the surface of the micron wire provide abundant sites and good channels for adsorption, mass transfer, and reaction, and provide abundant active sites; on the other hand, it blocks the contact between copper and electrolyte, and in alkaline solution, it can effectively inhibit the loss of copper, and exhibits excellent HMF / BHMF oxidation and hydrogen evolution activity and stability. Therefore, the characteristics of the copper-based micron wire make the copper-based electrocatalyst have excellent electrical conductivity, large specific surface area, high interface transfer efficiency, better catalytic activity and good stability, and have broad application potential and industrialization prospects in the fields of HMF / BHMF oxidation and electrolytic hydrogen production. The preparation method of the copper-based electrocatalyst provided by the present invention has simple equipment, easy-to-obtain raw materials, simple operation, and controllable conditions. After repeated experiments, it has good repeatability and is more suitable for the mass preparation of copper-based electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the preparation process of copper-based electrocatalysts.
[0031] Figure 2 is the XRD pattern of the copper-based electrocatalyst prepared in Example 1 ( Figure 2 e) Scanning electron microscope image ( Figure 2 a and Figure 2 b) Selected area electron diffraction pattern ( Figure 2 d) Transmission electron microscopy image ( Figure 2 c).
[0032] Figure 3 is the XPS of the copper-based electrocatalyst prepared in Example 1 ( Figure 3 a and Figure 3 b) and Raman ( Figure 3 c and Figure 3 d) Spectrum diagram.
[0033] Figure 4 is the oxygen evolution of the copper-based electrocatalyst prepared in Example 1 ( Figure 4 a) HMF oxidation ( Figure 4 b) BHMF oxidation ( Figure 4 c) and hydrogen evolution polarization curve ( Figure 4 d).
[0034] Figure 5 This is the kinetic test curve of the copper-based electrocatalyst prepared in Example 1.
[0035] Figure 6is the HMF of the copper-based electrocatalyst prepared in Example 1 ( Figure 6 a) and BHMF primary electrolysis curve ( Figure 6 b).
[0036] Figure 7 is the Raman graph of the electrocatalyst obtained in Example 7 after reaction ( Figure 7 a and Figure 7 b) Scanning electron microscope image ( Figure 7 c and Figure 7 d). DETAILED DESCRIPTION
[0037] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0038] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0039] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0040] Example 1
[0041] This embodiment provides a method for preparing a self-supporting monolithic copper-based electrocatalyst, comprising the following steps: (1) The cut copper foam was ultrasonically treated in acetone, ethanol, sulfuric acid and water for 30 min respectively, and then immersed in 1M KOH solution. The immersion area of the copper foam in the KOH solution was 0.5*2 cm 2Then, a constant current electrochemical oxidation was performed in a three-electrode device to in situ grow copper hydroxide microwires on the copper foam. The electrochemical oxidation current was 20 mA cm -2 , the time is 30 min, the three electrodes are working electrode foam copper, counter electrode platinum electrode, reference electrode Hg / HgO electrode; (2) In step (1), the copper hydroxide microwires were subjected to two electrochemical reduction reactions in a 1 M KOH solution. The first electrochemical reduction reaction was performed by cyclic voltammetry at a potential of -0.6 to -1.6 V vs. Hg / HgO and a scan rate of 50 mV s -1 , 50 cycles; the second electrochemical reduction reaction adopts constant potential method, the potential is -3 V vs. Hg / HgO, the time is 10 min, and the copper hydroxide microwires are reduced to form copper microwires; (3) The copper microwires in step (2) were subjected to electrochemical oxidation in a 1 M KOH solution using cyclic voltammetry at a potential of -0.3 to 0.8 V vs. Hg / HgO and a scan rate of 50 mV s -1 , and cycled 50 times to oxidize the surface of the copper microwires to form copper oxide nanosheets, obtaining copper-based microwires in situ grown on copper foam, which were then dried in an oven at 50 °C for 20 h to obtain a copper-based electrocatalyst.
[0042] Figure 1 Schematic diagram of the preparation process of copper-based electrocatalysts. As shown in the figure, copper foam (Cu foam, CF) is electrochemically oxidized to form copper hydroxide microwires (O-Cu x / CF), copper hydroxide microwires on the surface of copper foam are electrochemically reduced to form copper microwires (Cu x / CF), the copper microwires on the surface of the copper foam are then activated by electrochemical oxidation to form copper oxide nanosheets on the surface of the copper microwires, and a copper-based microwire electrocatalyst (R-Cu) is obtained, which is in situ grown on the copper foam and has copper inside and copper oxide nanosheets on the surface. x / CF、cvR-Cu x / CF).
[0043] Figure 2 is the XRD pattern of the copper-based electrocatalyst prepared in this embodiment ( Figure 2 e) Scanning electron microscope image ( Figure 2 a and Figure 2 b) Selected area electron diffraction pattern ( Figure 2 d) Transmission electron microscopy image ( Figure 2 c). From the scanning electron microscope image at low magnification ( Figure 2 The structure of the micrometer wire can be clearly seen in the scanning electron microscope image at high magnification ( Figure 2As can be seen in a), a large number of nanosheets are formed on the surface of the microwire. From the XRD pattern ( Figure 2 e) It can be seen that the diffraction peaks in the figure correspond to JCPDS standard cards 65-9026 (Cu), 65-3288 (Cu2O) and 45-0937 (CuO), indicating the presence of copper-based electrocatalysts in Cu, Cu2O and CuO. Figure 2 d) and high magnification TEM images ( Figure 2 c) It can be seen that the copper-based micron-wire electrocatalyst has a micron-wire morphology covered with nanosheets on the surface, and its phases are copper oxide on the surface and elemental copper inside.
[0044] Figure 3 is the XPS of the copper-based electrocatalyst prepared in this example ( Figure 3 a and Figure 3 b) and Raman ( Figure 3 c and Figure 3 d) Spectra. XPS ( Figure 3 a and Figure 3 b) and Raman ( Figure 3 c and Figure 3 d) Spectrum showing that the surface of the copper-based microwire electrocatalyst supported on copper foam is CuO.
[0045] The self-supporting monolithic copper-based microwire electrocatalyst prepared in this example was used as a working electrode to form a three-electrode system in an alkaline system for testing electrochemical properties, with a Hg / HgO electrode as a reference electrode, a platinum sheet as a counter electrode, and a 1.0 mol / L KOH solution as an electrolyte to form the three-electrode system.
[0046] Figure 4 is the oxygen evolution of the copper-based electrocatalyst prepared in this embodiment ( Figure 4 a) HMF oxidation ( Figure 4 b) BHMF oxidation ( Figure 4 c) and hydrogen evolution polarization curve ( Figure 4 d). The activity comparison between the preferred catalyst and pure copper (copper foam) was investigated by polarization curve test. The test equipment was an electrochemical workstation (Costech). The test device was a three-electrode electrolyzer, with the catalyst as the working electrode, the Pt sheet electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. The potential range was set to -0.3~0.8 V, and the scan rate was 5 mV / s. After adding 10 mM HMF, the current density reached 50 mA cm at 1.46 V vs. RHE. -2 , which is 200 mV earlier than 1.66 V vs. RHE in 1 M KOH. After adding 50 mM HMF, the current density can reach 50 mA cm at a low value of 1.39 V vs. RHE. -2Similarly, the potential increases after the addition of BHMF, reaching about 400 mA cm -2 The potential required for the current density is only 1.57 V vs. RHE. The test shows that the self-supporting monolithic copper-based microwire electrocatalyst has good HMF, BHMF oxidation performance and hydrogen evolution performance.
[0047] Figure 5 The kinetic test curve of the copper-based electrocatalyst prepared in this example is shown in Figure 2. A three-electrode device was used, with the copper-based electrocatalyst as the working electrode (the portion immersed in the solution was 0.5 cm 2 ), Pt sheet electrode is the counter electrode, and Hg / HgO electrode is the reference electrode. Figure 5 a is the electrochemical impedance spectroscopy test, from which it can be seen that the self-supporting monolithic copper-based electrocatalyst has a low resistance, and after adding HMF, the resistance is further reduced. Figure 5 b is the Tafel slope. A lower Tafel slope indicates that the copper-based electrocatalyst is more polarizable than foamed copper. Figure 5 c. Figure 5 d is the double-layer capacitance test, which shows that the copper-based electrocatalyst has a higher double-layer capacitance and a larger electrochemical active area, and after adding HMF, the double-layer capacitance increases. Figure 5 It can be seen that lower resistance and higher electrochemical active area make the copper-based electrocatalyst have good catalytic activity.
[0048] Figure 6 is the HMF of the copper-based electrocatalyst prepared in Example 1 ( Figure 6 a) and BHMF primary electrolysis curve ( Figure 6 b) The electrolysis capacity of copper-based electrocatalysts was investigated using a three-electrode device. The copper-based catalyst was used as the working electrode (the portion immersed in the solution was 0.5 cm 2 ), Pt sheet electrode is the counter electrode, and Hg / HgO electrode is the reference electrode. Figure 6 The catalyst has good catalytic activity. When 50 mM HMF is electrolyzed, the HMF conversion rate is 100% and the FDCA yield is 97.2%. In addition, the catalyst can also electrolyze BHMF. When 50 mM BHMF is electrolyzed, the final BHMF conversion rate is 100% and the FDCA yield is 95.3%. In addition, the Raman graph of the copper-based electrocatalyst after the reaction ( Figure 7 a and Figure 7 b) Scanning electron microscope image ( Figure 7 c and Figure 7 d) It can be seen that there is no obvious change in the surface oxidation state and morphology of the catalyst, which illustrates the stability of the catalyst.
[0049] Example 2 This embodiment provides a method for preparing a self-supporting monolithic copper-based electrocatalyst, comprising the following steps: (1) The cut copper foam was ultrasonically treated in acetone, ethanol, sulfuric acid and water for 60 min respectively, and then immersed in 2M KOH solution. The immersion area of the copper foam in the KOH solution was 2*2 cm 2 Then, a constant current electrochemical oxidation was performed in a three-electrode device to in situ grow copper hydroxide microwires on the copper foam. The electrochemical oxidation current was 40 mA cm -2 , the time is 30 min, the three electrodes are working electrode foam copper, counter electrode platinum electrode, reference electrode Hg / HgO electrode; (2) In step (1), the copper hydroxide microwires were subjected to two electrochemical reduction reactions in a 2 M KOH solution. The first electrochemical reduction reaction was performed by cyclic voltammetry at a potential of -0.4 to -2 V vs. Hg / HgO and a scan rate of 100 mV s -1 , 100 cycles; the second electrochemical reduction reaction adopts constant potential method, the potential is -2 V vs. Hg / HgO, the time is 20 min, and the copper hydroxide microwires are reduced to form copper microwires; (3) The copper microwires in step (2) were subjected to electrochemical oxidation in a 2 M KOH solution using cyclic voltammetry at a potential of -0.3 to 0.8 V vs. Hg / HgO and a scan rate of 100 mV s -1 , and cycled 100 times to oxidize the surface of the copper microwires to form copper oxide nanosheets, obtaining copper-based microwires in situ grown on copper foam, which were then dried in an oven at 80 °C for 15 h to obtain a copper-based electrocatalyst.
[0050] The results of characterization of its structure and morphology by X-ray diffraction and scanning and transmission electron microscopy showed that a self-supporting monolithic copper-based electrocatalyst was obtained. XPS and Raman spectroscopy further verified that its surface was copper oxide. Electrochemical performance tests, kinetic tests, HMF and BHMF electrolysis tests and SEM after the reaction showed that the copper-based electrocatalyst had good HMF oxidation and hydrogen evolution activity and stability.
[0051] Example 3
[0052] This embodiment provides a method for preparing a self-supporting monolithic copper-based electrocatalyst, comprising the following steps: (1) The cut copper foam was ultrasonically treated in acetone, ethanol, sulfuric acid and water for 10 min in sequence, and then immersed in 5M KOH solution. The immersion area of the copper foam in the KOH solution was 10*10 cm 2Then, constant current electrochemical oxidation was performed in a three-electrode device to in situ grow copper hydroxide microwires on the copper foam. The electrochemical oxidation current was 200 mA cm -2 , time is 2 min, the three electrodes are working electrode foam copper, counter electrode platinum electrode, reference electrode Hg / HgO electrode; (2) In step (1), the copper hydroxide microwires were subjected to two electrochemical reduction reactions in a 5 M KOH solution. The first electrochemical reduction reaction was performed by cyclic voltammetry at a potential of -0.8 to -2.4 V vs. Hg / HgO and a scan rate of 2 mV s -1 , 5 cycles; the second electrochemical reduction reaction was carried out using a constant potential method, with a potential of -5 V vs. Hg / HgO and a time of 10 min. The copper hydroxide microwires are reduced to form copper microwires; (3) The copper microwires in step (2) were subjected to electrochemical oxidation in a 5 M KOH solution using cyclic voltammetry at a potential of -0.3 to 0.8 V vs. Hg / HgO and a scan rate of 2 mV s -1 , and cycled for 5 times to oxidize the surface of the copper microwire to form copper oxide nanosheets, thereby obtaining copper-based microwires in situ grown on copper foam, which were then dried in an oven at 70 °C for 10 h to obtain a copper-based electrocatalyst.
[0053] The results of characterization of its structure and morphology by X-ray diffraction and scanning and transmission electron microscopy showed that a self-supporting monolithic copper-based electrocatalyst was obtained. XPS and Raman spectroscopy further verified that its surface was copper oxide. Electrochemical performance tests, kinetic tests, HMF and BHMF electrolysis tests and post-reaction SEM showed that the copper-based electrocatalyst had good HMF oxidation and hydrogen evolution activity and stability.
[0054] Example 4
[0055] This embodiment provides a method for preparing a self-supporting monolithic copper-based electrocatalyst, comprising the following steps: (1) The cut copper foam was ultrasonically treated in acetone, ethanol, sulfuric acid and water for 60 min in sequence, and then immersed in 10 M KOH solution. The immersion area of the copper foam in the KOH solution was 50*50 cm 2 Then, a constant current electrochemical oxidation was performed in a two-electrode device to in situ grow copper hydroxide microwires on the copper foam. The electrochemical oxidation current was 1 mA cm -2 , time is 20 min, the double electrodes are working electrode copper foam and counter electrode platinum sheet electrode; (2) The copper hydroxide microwires in step (1) are subjected to an electrochemical reduction reaction in a 10 M KOH solution. The electrochemical reduction reaction adopts a constant voltage method with a voltage of -5 V and a time of 10 min. The copper hydroxide microwires are reduced to form copper microwires. (3) The copper microwires in step (2) were subjected to an electrochemical oxidation reaction in a 10 M KOH solution. The electrochemical oxidation reaction was carried out using a constant voltage method with a voltage of 2 V and a time of 20 min. Copper oxide nanosheets were oxidized on the surface of the copper microwires to obtain copper-based microwires grown in situ on the foam copper. The copper-based microwires were dried in an oven at 60° C. for 15 h to obtain a copper-based electrocatalyst.
[0056] The results of characterization of its structure and morphology by X-ray diffraction and scanning and transmission electron microscopy showed that a self-supporting monolithic copper-based electrocatalyst was obtained. XPS and Raman spectroscopy further verified that its surface was copper oxide. Electrochemical performance tests, kinetic tests, HMF and BHMF electrolysis tests and post-reaction SEM showed that the copper-based electrocatalyst had good HMF oxidation and hydrogen evolution activity and stability.
[0057] Example 5 This embodiment provides a method for preparing a self-supporting monolithic copper-based electrocatalyst, comprising the following steps: (1) The cut copper foam was ultrasonically treated in acetone, ethanol, sulfuric acid and water for 30 min in sequence, and then immersed in 0.1 M KOH solution. The immersion area of the copper foam in the KOH solution was 5*5 cm 2 Then, a constant current electrochemical oxidation was performed in a three-electrode device to in situ grow copper hydroxide microwires on the copper foam. The electrochemical oxidation current was 0.01 A cm -2 , time is 3 h, the three electrodes are working electrode foam copper, counter electrode platinum electrode, reference electrode Hg / HgO electrode; (2) In step (1), the copper hydroxide microwires were subjected to two electrochemical reduction reactions in a 0.1 M KOH solution. The first electrochemical reduction reaction was performed by cyclic voltammetry at a potential of 0 to -3 V vs. Hg / HgO and a scan rate of 200 mV s -1 , 500 cycles; the second electrochemical reduction reaction adopts constant potential method, the potential is -5 V vs. Hg / HgO, the time is 10 min, and the copper hydroxide microwires are reduced to form copper microwires; (3) The copper microwires in step (2) were subjected to electrochemical oxidation in a 0.1 M KOH solution. The electrochemical oxidation was performed using cyclic voltammetry at a potential of -0.3 to 0.8 V vs. Hg / HgO and a scan rate of 200 mV s -1, and circulated 500 times to oxidize the surface of the copper microwire to form copper oxide nanosheets, obtaining copper-based microwires in situ grown on foam copper, which were dried in an oven at 50 °C for 20 h to obtain a copper-based electrocatalyst.
[0058] The results of characterization of its structure and morphology using X-ray diffraction and scanning and transmission electron microscopy show that a self-supporting monolithic copper-based microwire electrocatalyst has been prepared. XPS and Raman spectroscopy further verify that its surface is copper oxide.
[0059] Electrochemical performance tests, kinetic tests, HMF and BHMF electrolysis tests and post-reaction SEM showed that the copper-based electrocatalyst has good HMF oxidation and hydrogen evolution activity and stability.
[0060] A copper-based electrocatalyst provided by the present invention can be prepared by a simple electrochemical method, and the solute involved only includes alkali; the obtained material is a copper-based micron wire derived in situ on a copper carrier, which is specifically characterized by a single copper core surface covered with copper oxide nanosheets. Under the optimal conditions, the conversion rate of electrolysis of 50 mM HMF is 100%, the FDCA yield is 97.2%, and the SEM after the reaction is consistent with that before the reaction, indicating that the material has good stability. The preferred copper carrier is foamed copper. Compared with other copper carriers, foamed copper has the advantages of high conductivity, large specific surface area, good adsorption and mass transfer. Since the active substance is derived in situ on the carrier surface and is reconstructed from the surface, it has a higher lattice fit, stronger binding force, stronger stability, and higher conductivity than coated and deposited catalysts. In addition, the equipment required for the present invention is simple, the raw materials are easily available, the operation is simple, the conditions are controllable, and after repeated experiments, it has good repeatability and is more suitable for mass production.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A copper-based electrocatalyst, characterized in that The invention consists of a copper carrier and a copper-based micron wire in-situ grown on the surface of the copper carrier. The interior of the copper-based micron wire is single copper, and the surface of the copper-based micron wire is a copper oxide nanosheet.
2. A method for preparing the copper-based electrocatalyst according to claim 1, characterized in that: The following steps are involved: S1. Electro-oxidation: The copper carrier is immersed in an alkaline solution to perform an electrochemical oxidation reaction, and copper hydroxide microwires are grown in situ on the copper carrier; S2, electro-reduction: the copper hydroxide micro-wires in step S1 are subjected to an electrochemical reduction reaction in the alkaline solution, and the copper hydroxide micro-wires are reduced to form copper micro-wires; S3, electroactivation: the copper microwires in step S2 are subjected to electrochemical oxidation reaction in the alkaline solution, and copper oxide nanosheets are formed on the surface of the copper microwires to obtain copper-based microwires grown in situ on a copper carrier, and a copper-based electrocatalyst is obtained through post-treatment.
3. The method for preparing a copper-based electrocatalyst according to claim 2, characterized in that: The electrical reduction in step S2 adopts a two-step reduction method, wherein the first step of reduction adopts a reduction-oxidation-reduction cyclic voltammetry reduction method, and the second step of reduction adopts a constant potential / constant current reduction method.
4. The method for preparing a copper-based electrocatalyst according to claim 2, characterized in that: The alkali in the alkali solution includes one or both of potassium hydroxide and sodium hydroxide; and / or, the concentration of the alkali solution is 0.1 to 10 M; And / or, the copper carrier comprises any one of foamed copper, copper tape, copper sheet, copper foil and electrodeposited copper.
5. The method for preparing a copper-based electrocatalyst according to claim 4, characterized in that: The copper carrier is foamed copper; And / or, the immersion area of the copper carrier in step S1 is 0.5*0.5~50*50 cm 2 ; And / or, in step S1, the copper carrier is first cleaned before being immersed in the alkali solution, and the cleaning method is to ultrasonically clean in acetone, ethanol, sulfuric acid and deionized water for 10 to 60 minutes in sequence.
6. The method for preparing a copper-based electrocatalyst according to claim 2, characterized in that: The electrochemical oxidation reaction in step S1, the electrochemical reduction reaction in step S2 and the electrochemical oxidation reaction in step S3 are carried out in a three-electrode system or a two-electrode system; in the three-electrode system, the working electrode is a copper support, the counter electrode is a carbon rod or a platinum electrode, and the reference electrode is a Hg / HgO electrode; in the two-electrode system, the working electrode is a copper support, and the counter electrode is a carbon rod or a platinum electrode; and / or, the reaction time of the electrochemical oxidation reaction in step S1, the electrochemical reduction reaction in step S2 and the electrochemical oxidation reaction in step S3 is 0.1 to 3 h; And / or, the post-treatment in step S3 is performed by drying in an oven at 50-100° C. for 5-20 h.
7. The method for preparing a copper-based electrocatalyst according to claim 6, characterized in that: When the three-electrode system is used, the electrochemical oxidation reaction in step S1 adopts a constant current / constant potential electrochemical oxidation method, and the current / potential range is 0.01 to 1 A cm -2 / 1~3 V vs. Hg / HgO; And / or, when the three-electrode system is used, the electrochemical reduction reaction in step S2 is a two-step reaction, the first step is cyclic voltammetry, the potential of the cyclic voltammetry is 0 to -3 V vs. Hg / HgO, and the second step is constant current / constant potential method, the current / potential range is -0.1 to -3 A cm -2 / -1~-5 V vs. Hg / HgO; And / or, when the three-electrode system is used, the electrochemical oxidation reaction in step S3 is carried out by cyclic voltammetry, and the potential of the cyclic voltammetry is -0.6~1.6 V vs. Hg / HgO.
8. The method for preparing a copper-based electrocatalyst according to claim 7, characterized in that: The scanning speed of the cyclic voltammetry method is 2 to 200 mV s-1, and the scanning number is 5 to 500 circles.
9. The method for preparing a copper-based electrocatalyst according to claim 6, characterized in that: When the dual-electrode system is used, the electrochemical oxidation reaction in step S1 adopts a constant current / constant voltage method, and the current / voltage range is 0.01 to 1 A cm -2 / 0.5~2 V; And / or, when the dual-electrode system is used, the electrochemical reduction reaction in step S2 adopts a constant current / constant voltage method, and the current / voltage range is -0.1 to -3 A cm -2 / -1~-5 V; And / or, when the dual-electrode system is used, the electrochemical oxidation reaction in step S3 adopts a constant voltage method with a voltage range of 0.5 to 2 V.
10. Use of the copper-based electrocatalyst according to claim 1 in the electrocatalytic oxidation of HMF / BHMF to produce FDCA and electrolytic hydrogen production.
Citation Information
Cited By
Intermittent stop-based copper-based electrocatalyst regeneration method
CN121826798A